Characterization of the Staphylococcus xylosus methylome reveals a new variant of type I restriction modification system in staphylococci - Schiffer, Carolin J.; Grätz, Christian; Pfaffl, Michael W.; Vogel, Rudi F.; Ehrmann, Matthias A. (Frontiers in Microbiology, 2023)
Restriction modification (RM) systems are known to provide a strong barrier to the exchange of DNA between and within bacterial species. Likewise, DNA methylation is known to have an important function in bacterial epigenetics regulating essential pathways such as DNA replication and the phase variable expression of prokaryotic phenotypes. To date, research on staphylococcal DNA methylation focused mainly on the two species Staphylococcus aureus and S. epidermidis. Less is known about other members of the genus such as S. xylosus, a coagulase-negative commensal of mammalian skin. The species is commonly used as starter organism in food fermentations but is also increasingly considered to have an as yet elusive function in bovine mastitis infections. We analyzed the methylomes of 14 S. xylosus strains using single-molecular, real-time (SMRT) sequencing. Subsequent in silico sequence analysis allowed identification of the RM systems and assignment of the respective enzymes to the discovered modification patterns. Hereby the presence of type I, II, III and IV RM systems in varying numbers and combinations among the different strains was revealed, clearly distinguishing the species from what is known for other members of the genus so far. In addition, the study characterizes a newly discovered type I RM system, encoded by S. xylosus but also by a variety of other staphylococcal species, with a hitherto unknown gene arrangement that involves two specificity units instead of one (hsdRSMS). Expression of different versions of the operon in E. coli showed proper base modification only when genes encoding both hsdS subunits were present. This study provides new insights into the general understanding of the versatility and function of RM systems as well as the distribution and variations in the genus Staphylococcus.